1999
DOI: 10.1136/pgmj.75.888.599
|View full text |Cite
|
Sign up to set email alerts
|

General hospital services for deliberate self-poisoning: an expensive road to nowhere?

Abstract: SummaryThis study was designed to investigate the clinical and economic aspects of deliberate self-poisoning services in four teaching hospitals in Leeds, Leicester, Manchester and Nottingham. We investigated the management of the current selfharm episode, including direct in-hospital costs, in 456 individuals who presented to hospital on a total of 477 occasions with deliberate self-poisoning during a 4-week period in 1996. Fewer than half of the patients received specialist psychosocial assessment or follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 14 publications
(13 reference statements)
0
36
1
1
Order By: Relevance
“…This is defined as an integrated assessment of needs and risk (National Collaborating Centre for Mental Health, 2004). It may improve access to aftercare (Barr, Leitner, & Thomas, 2005;Kapur, House, Creed et al, 1999) and protect against self-harm repetition (Kapur, House, May et al, 2003;Kapur, Murphy, Cooper et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is defined as an integrated assessment of needs and risk (National Collaborating Centre for Mental Health, 2004). It may improve access to aftercare (Barr, Leitner, & Thomas, 2005;Kapur, House, Creed et al, 1999) and protect against self-harm repetition (Kapur, House, May et al, 2003;Kapur, Murphy, Cooper et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Although several researchers have examined the factors associated with nonassessment, which include attendance outside working hours; discharge by hospital staff; younger age; cutting as a method of harm; and not being in contact with psychiatric services (Barr, Leitner, & Thomas, 2005;Bennewith, Peters, Hawton et al, 2005;Hickey, Hawton, Fagg et al, 2001;Kapur, House, Creed et al, 1999;Kapur, Murphy, Cooper et al, 2008); less is known about subsequent compliance with aftercare.…”
Section: Introductionmentioning
confidence: 99%
“…A study that compared the hospital costs relating to cases of intentional self-injury in different British hospitals showed that the costs were 33% higher when care was provided at university hospitals. 32 The length of follow-up was also a limiting factor for the present study. The three-month period characterizes the acute phase for both of these pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have included different age ranges in the same sample. 26,27,32,36 For example, it is known that studies that analyzed the cost of suicidal behavior during adolescence have found relatively low costs. 37,39 The majority of such studies only included a description of the hospital cost, and the elements considered in such evaluations were not homogenous among studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation